Equity valuation: EDP – Energias de Portugal, S.A - Rafael, Miguel Micaelo Barata (2021)
EDP S.A. is a Portuguese company, vertically integrated, present in the entirety of the electricity value chain and gas commercialization activity. The purpose of this project is to compute the fair equity value of EDP – Energias de Portugal, S.A on the 31st of December of 2020 and ultimately compare it to the market price. Following an extensive theoretical review of the main equity valuation methods and accounting to practitioners’ preferences and overall fit to the company in study, the methods chosen were the Free Cash Flow to the Firm and Relative Valuation. Furthermore, a sensitivity analysis was carried to take into account possible variations in key drivers of the valuation. Although the valuation will be thoroughly and carefully done, taking into consideration the newest quantitative and qualitative information and the most impactful literature on the subject, it will nonetheless still be a debatable subject, due to the nature of equity valuation exercises. The outcome of the valuation methods applied are coherent and suggest that the fair value of EDP’s shares is higher than its market value as of 31st of December 2021.